Methadone for Opioid Use Treatment during Pregnancy: Trends in Postpartum Dose Adjustments - Clara Ward; Carl W. Christensen (Thieme Medical Publishers, Inc., 2020)
Objective This study examines methadone dose adjustment postpartum. Methods A retrospective study of women with methadone for opioid use treatment (OUT) during pregnancy was performed. Patient charts were reviewed and data were extracted. Methadone doses from five temporal data points for each patient were used: starting dose, day of delivery, and 1, 2, and 6 months postpartum. Results Over 26 months, 49 pregnancies to women using methadone for OUT were evaluated and 20 (41%) were included. The mean methadone starting dose was 47 mg, compared with 86 mg at the time of delivery. The mean dose postpartum remained unchanged from delivery and 75% of pregnancies required the same dose or higher 1 month postpartum. By 2 months postpartum, only 33% were able to decrease their methadone dose. Twelve pregnancies completed follow-up until 6 months postpartum; only 17% of patients were able to decrease their dose, with an overall mean dose decrease was 12%. There was no difference between the mean dose at delivery and the 6-month postpartum dose. Conclusion Patients using methadone for OUT during pregnancy achieved minimal dose decreases postpartum. Patients should be counseled that postpartum dose tapers may be challenging and about alternatives to methadone for OUT.